Industrial crops : breeding for bioenergy and bioproducts (2015)
Industrial Crops is the ninth book of the Handbook of Plant Breeding series. This volume focuses on the emerging areas of plant breeding for sustainable production of transportation fuels and biobased products using the current advances in the field. Individual chapters discuss crops being considered for different challenge areas such as oil crops for biodiesel; sugar, starch and cellulosic crops for biofuel; crops for bioproducts; and issues and future prospects. Specific issues covered encompass available germplasm, breeding techniques, and potential geographical areas of production for industrial uses. Outstanding scientists representing various national and international institutions contributed chapters within their expertise for each crop species. Diverse views and solutions are presented on the common issues that researchers on industrial crops are facing. This book serves as an up-to-date reference to researchers in both academic and industrial setting, to students and teachers of plant breeding, and to policy makers who are looking for alternative solutions to dependency on imported petroleum products.--
Keywords: Plant breeding; Plant products; Field crops; Biomass energy